Reacciones adversas medicamentosas del enalapril y del nifedipino observadas en el servicio de geriatría del Hospital Central Luis N. Sáenz de la Policía Nacional del Perú, Lima 1999 - Moyano Legua, Rosa Danítza (2002)
This study was carried out from January to June of the year 1999, with the objective of describing the adverse reactions of the enalapril and nifedipino in the older adult hypertense that attend the service of Gerialrics of the HCLNSPNP.It was distributed to the patients, a questionnairc with the purpose of obtaining information of the variable sociodemografics (age, sex, occupation) as well as the form of presentation of the probable adverse reactions.Of 135 patients that received enalapril: 12 presented probable adverse reactions (sickness, Migraine and dyspepsia) and of 12 patients treated with nifedipino: 4 patients presented possible adverse reactions (migraine, sensation of heat, facial reddishness); what means the 6.47% of the population sample.The data was analyzed using the statistical package SPSS versión 9,0.Conclusions: The older adult has more probability of being more susceptiblc to secondary effects or adverse reactions for the enalapril administration or of nifedipino.